“Producción de cebolla (Allium fistolos um L.) Var roja chiclayana con aplicación de tres fuentes y tres dosis de abono orgánico, en la provincia de Lamas, departamento de San Martín” - Apomayta Julca, Gino Paolo (2011)
This research work was carried out with the effect of three sources and three doses of compost manure at a rate of 20 tons I ha, to 15Tn/ha manure, chicken manure to 10Tn/ha, Vacaza to 20Tn/ha, Vacaza to 15Tn I ha, and cuyaza Vacaza to 1 OTn/ha to 20Tn/ha, cuyaza to 15Tn/ha, cuyaza to 1 OTn/ha to determine which of them has the best results in growth performance and health in China organically grown onions (Allium fistolosum L.) in the estate called "Pacific Fundo", owned by Jorge L. Peláez Rivera, located in Sector Killoallpa, district and province of Lamas in the region of San Martin, at Latitude 06 ° 20'15 South, 'West Longitude 76 ° 30'45", altitude 814 m was conducted under the complete block design random (RCBD) with factorial arrangement 3 x 4, we evaluated the percentage of seedling emergence, plant average height, average number of bulbs per plant, average weight per plant, yield kg I ha dry matter in economic analysis. The results were subjected to analysis of variance and Duncan test of means. The factors A (source), B (dose) and the interaction between these separately. With the result that with all treatments the soil and the production was better than in normal conditions whose treatment was No. 12 on what works best tube with respect to product quality and performance of this but the high cost of production shows that not the best treatment from the economic point of view that we need more investment and profits are lower than the treatment No. 4 which tube lower performance and nearly the same quality and cost of production of this is much less than the treatment N ° 12. The application of these composts the manure from the Vacaza cuyaza and in mixtures with efficient bodies have influenced the growth and development of the plant, and it improved the physical structure and electrical conductivity, pH and conductivity of cation exchange MO content increased, P205, K20, Ca + +, Mg in soil after harvest.